2022
DOI: 10.1016/j.chest.2022.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Life Support and Advance Care Planning During the COVID-19 Pandemic

Abstract: Background The COVID-19 pandemic has presented new challenges surrounding end-of-life planning and has been associated with increased online discussion about life support. Research Question How has online communication about advance care planning (ACP) and specific life-sustaining interventions (LSIs) changed during the pandemic? Study Design and Methods Conversations on Twitter containing references to LSIs (e.g., ‘ECMO’) or ACP (e.g., ‘DNR/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The public awareness on the COVID-19-associated mortality, especially among the elder population, was substantial. As indicated by recent data from social media platforms, the COVID-19 pandemic led to a considerable increase of communication about ICU-specific life-sustaining treatments and advance care planning [ 15 ]. It is unclear whether the public awareness might have triggered potential early discussions of advance care planning.…”
Section: Introductionmentioning
confidence: 99%
“…The public awareness on the COVID-19-associated mortality, especially among the elder population, was substantial. As indicated by recent data from social media platforms, the COVID-19 pandemic led to a considerable increase of communication about ICU-specific life-sustaining treatments and advance care planning [ 15 ]. It is unclear whether the public awareness might have triggered potential early discussions of advance care planning.…”
Section: Introductionmentioning
confidence: 99%
“…In CHEST (June 2022), Patel et al 7 use a novel big data approach to measure patient perceptions of ACP through machine learning (ML). By applying natural language processing (NLP) to Twitter metadata, they found that public discussion of ACP and life-sustaining interventions (LSIs) both increased during the early days of the pandemic in spring of 2020 but that ACP messages were viewed less frequently and more negatively than discussions of LSIs.…”
mentioning
confidence: 99%
“…Patel et al 7 were able to exploit Twitter metadata to apply ML techniques to Twitter. Historic data on the social media platform retains information about the short-form 280-character messages (“tweets”), including who viewed them, whether the messages were “re-tweeted” by followers, and user demographic characteristics such as geolocation.…”
mentioning
confidence: 99%
See 2 more Smart Citations